Effect of admixtures and supplementary cementitious material on mechanical properties and durability of concrete. Issue 1 (24th March 2020) - Asadollahfardi, Gholamreza; Yahyaei, Behnaz; Salehi, Amir M.; Ovesi, Arash
Abstract: We studied the effects of superplasticizer (SP) (PCE1 and PCE2), air‐entraining admixtures (AEA), and supplementary cementitious material (silica fume and fly ash) on the mechanical and durability properties of concrete samples. Eight concrete mix designs were prepared. The first six concrete mix design contained similar aggregates, PCE2 SP, AEA, 350 kg/m 3 cement, and water to cement ratio equal to 0.38, and one of the mentioned mix design was selected as control samples with water to cement ratio equal to 0.57, without PCE2 SP and AEA. We used a different quantity of PCE2 SP and AEA and replaced the fly ash or silica fume as part of cement in two of the mentioned mix designs. The last two concrete mix designs studied the effect of PCE1 SP and AEA on freezing and thawing of concrete mix design. Adding PCE2 SP in concrete mix design increased compressive strength at age 11, 42, and 90 days sharply and reduced the depth of water penetration at the age of 28 and 90 days compared to the control sample. Using simultaneous PCE2 and AEA in concrete mix design did not improve compressive strength significantly and increased slightly depth of water penetration compared to only using PCE2. However, increasing the quantity of AEA to 5% improved both compressive strength and reduced depth of water penetration. In the second group of concrete mix design, adding both PCE1 and AEA increased the number of resistible freezing and thawing cycles of concrete. Side chain length and molecular weight of PCE1 and PCE2 SPs had no important effect on the compressive strength and performance properties of concrete.